2000
DOI: 10.1897/1551-5028(2000)019<1624:riocam>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Relative Importance of Calcium and Magnesium in Hardness-Based Modification of Copper Toxicity

Abstract: Abstract-Because of the relationship between water hardness and the toxicity of many metals, total hardness is used as a model parameter to calculate ambient water quality criteria for copper and other metals. However, the relative contribution of the Ca and Mg components of total hardness as modifiers of metals toxicity is not considered in the water quality criteria. Acute Cu toxicity was measured in rainbow trout (Oncorhynchus mykiss) and chinook salmon (O. tshawytscha) swim-up fry in laboratory waters that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 18 publications
1
44
0
Order By: Relevance
“…We estimated log K Mg-gillAg ϭ 3.0, which yielded results close to what was seen experimentally. This twofold lower protection compared to Ca agrees well with the relative protective effects of Ca and Mg for metals in general (e.g., for Cu [23,24]).…”
Section: Discussionsupporting
confidence: 84%
“…We estimated log K Mg-gillAg ϭ 3.0, which yielded results close to what was seen experimentally. This twofold lower protection compared to Ca agrees well with the relative protective effects of Ca and Mg for metals in general (e.g., for Cu [23,24]).…”
Section: Discussionsupporting
confidence: 84%
“…Although relationships between water-chemistry characteristics and aquatic copper toxicity have been investigated previously [12][13][14][15][16][17][18][19], to our knowledge only two studies with Daphnia magna have used soft waters [20,21]. Long et al [20] showed that hardness influenced copper toxicity to D. magna but found no effect of pH, and Villavicencio et al [21] showed an important effect of DOC concentration on LC50s for Daphnia obtusa and D. magna in reconstituted soft waters.…”
Section: Introductionmentioning
confidence: 99%
“…; Heirjerick et al, 2002, Gensemer et al, 2002Welsh et al, 2000aWelsh et al, , 2000b. BLM constants should be worked out directly by experimentation on the organisms of interest.…”
Section: +mentioning
confidence: 99%